1997
DOI: 10.1063/1.120401
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature formation of C54–TiSi2 using titanium alloys

Abstract: We demonstrate that the temperature at which the C49 TiSi2 phase transforms to the C54 TiSi2 phase can be lowered more than 100 °C by alloying Ti with small amounts of Mo, Ta, or Nb. Titanium alloy blanket films, containing from 1 to 20 at. % Mo, Ta, or Nb were deposited onto undoped polycrystalline Si substrates. The temperature at which the C49–C54 transformation occurs during annealing at constant ramp rate was determined by in situ sheet resistance and x-ray diffraction measurements. Tantalum and niobium a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 9 publications
2
38
0
Order By: Relevance
“…Titanium Silicides suffered from difficulties in forming the low resistivity phase on narrow poly lines, as well as its silicon diffusion dominated formation of Silicides leading to bridging problems [302][303][304][305]. There are several methods to solve this problem, such as, refractory metal Nb, Ta or Mo alloyed with Ti or implanted into silicon, or introducing a thin refractory metal layer between titanium and silicon before thermal annealing [306,307]. The refractory metal Silicide will promote the low-resistivity phase formation by a template effect [308].…”
Section: Fully Silicided (Fusi) Gatesmentioning
confidence: 99%
“…Titanium Silicides suffered from difficulties in forming the low resistivity phase on narrow poly lines, as well as its silicon diffusion dominated formation of Silicides leading to bridging problems [302][303][304][305]. There are several methods to solve this problem, such as, refractory metal Nb, Ta or Mo alloyed with Ti or implanted into silicon, or introducing a thin refractory metal layer between titanium and silicon before thermal annealing [306,307]. The refractory metal Silicide will promote the low-resistivity phase formation by a template effect [308].…”
Section: Fully Silicided (Fusi) Gatesmentioning
confidence: 99%
“…1,2 The vexatious problem with the formation of the desired low-resistivity C54 phase of TiSi 2 ͑15-20 ⍀ cm͒ has resulted in the use of other low-resistivity silicides such as CoSi 2 and NiSi in electronic devices, 2-4 although significant improvements in enhancing the C54 phase formation at lower temperatures have been shown by incorporation of refractory metals in the Ti-Si system [5][6][7][8][9] or by amorphization of the Si prior to silicidation. 10 The low formation temperature ͑below 500°C͒, low Si consumption during silicidation, low resistivity ͑14 -20 ⍀ cm͒, low contact resistivity to both types of Si and no reported dependence of phase formation on geometrical dimensions have made NiSi an attractive alternative for electrical contacts in sub-100 nm CMOS technology.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, it has been demonstrated that the nucleation of metal silicides is significantly influenced by the presence of an interposing metal layer [6][7][8][9], a capping layer [10,11], and alloying elements [12][13][14][15]. For the formation of CoSi 2 thin films, recent studies have shown that the nucleation temperature of CoSi 2 was found to be dramatically lowered in the presence of small amounts of Au [8,16,17].…”
Section: Introductionmentioning
confidence: 98%